From the Editor - Hahn, Stefan (Archives of Acoustics, 1991)
The conferences on piezoelectronics are nearly regularly organized in Poland since 1968. This volume contains selected papers presented at the VII-th Conference on Piezoelectronics which was held on April 25-27, 1990 at Serock near Warsaw. Some of them were delivered to the Programme Committee in polish and russian language and were translated to english on behalf the editors of this volume. The content shows that piezoelectronics is still a developing branch of science and technology far from saturation. A big effort is containning in developing new piezoelectronic sensors of various physical and chemical quantities. Piezoelectric resonators are continuously expanding into the microwave frequency region. Thin films piezoelectric structures find new applications. These is also a continuous effort to develop new piezoelectric materials. The edition of this volume was possible thanks to the editors of Archives of Acoustics and the support given by Institute of Fundamental Technological Research of the Polish Academy of Sciences.